POTENSI PERTUMBUHAN DAN DAYA SAING SEKTOR PERTAMBANGAN DI KABUPATEN MANOKWARI - Setiawan, Arif; Rosyid, Fadhila Achmadi (Jurnal Teknologi Mineral dan Batubara, 2024)
The mining sector is a sector that contributes to economic growth in areas, one of which is in the Manokwari Regency. Within 12 years (2010-2022) the GRDP of the mining sector is likely to increase. The GRDP of the mining sector contributes 3% of the total GRDP of the Manokwari regency. Based on this, does the mining sector have the potential and the carrying capacity or competitiveness in the increasing GRDP in the Manokwari Regency? Therefore, this study aims to assess the potential and carrying capacity of the mining sector in increasing economic growth in the Manokwari regency. The method used is overlay analysis, which results from a combination of the assessment methods of Static Location Questient, Dynamic Location Questient, Shift Share Analysis, Typology Classen analysis, and Growth Ratio Models. The data used is GRDP data for Manokwari Regency and West Papua Province from 2010 to 2022. The results obtained show that the mining sector in Manokwari Regency is not the main sector or has not become the main focus in Manokwari Regency. However, this sector is a prospective sector or has the potential to be developed in the future so that it becomes the mainstay sector or the main sector.